Case Report: Intraocular Hemorrhage in a Primary Vitreoretinal Lymphoma Patient Treated With Zanubrutinib - Zhang, Xiao; Dai, Rongping; Zhao, Chan; Zhang, Meifen (Frontiers in Medicine, 2022)
Purpose To report a case of primary vitreoretinal lymphoma (PVRL) treated with oral zanubrutinib, who had bilateral intraocular hemorrhage after intravitreal injection of methotrexate (MTX). Case report A 69-year-old Chinese female presented with vision decrease in both eyes. After diagnostic vitrectomy, the patient was diagnosed as PVRL in both eyes, and was treated with intravenous rituximab, oral zanubrutinib and bilateral intravitreal MTX. There were bilateral anterior chamber and vitreous hemorrhage after the fourth intravitreal MTX combined with paracentesis. After discontinuation of zanubrutinib, vitrectomy and silicon oil tamponade were performed on the left eye, and the blood in the right eye was absorbed. Conclusion Bleeding is a major concern in the use of zanubrutinib. It is suggested that drugs be held for a few days prior to procedures and surgeries.